EVALUATION OF NON-PERMANENT AND PERMANENT REGIME MODELS FOR CALCULATION OF DRAIN SPACING - Tavares, L. C. M.; Araújo, G. M.; dos Santos, F. F. L.; Colares, A. P. F.; Braga, A. F.; Rosas, J. T. F. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The growing demand for food and techniques that make feasible the agronomic and economic exploration of areas with problems caused by excess water in the soil are some of the reasons that justify the use of drainage. In agricultural drainage, the drains are usually installed on or above the impermeable layer, the depth of installation of drains, drainage porosity and hydraulic conductivity being important parameters in the calculation of drain spacing. This calculation can be carried out using different methods. However, some methodologies apply better to a given rain regime than others. In this context, this work aimed to evaluate different equations used to estimate the spacing of drains under a variable and permanent flow regime. By means of the analysis of the Average Quadratic Deviation of the models, a comparison was established referring to the precision of each model. Any of the models for non-permanent regime can be used. While for the permanent regime, the worst model was Kirkham, and the other models showed statistically equal mean square deviations.